207 PEDIATRIC APPENDICITIS TREATED BY PEDIATRIC VERSUS GENERAL SURGEONS: A COMPARISON OF PATIENT CHARACTERISTICS AND OUTCOMES. (1st January 2006) - Emil, S.; Taylor, M.; Ndiforchu, F.; Nguyen, N.; Wilson, S.
Abstract : Hypothesis: Pediatric appendicitis is treated by both pediatric and general surgeons. We investigated whether specialty-dependent differences existed in patients' characteristics and outcomes. Design: Retrospective chart review. Setting: University-affiliated children's hospital, attached to a general hospital. Patients: 465 consecutive children (up to the 18th birthday) treated for appendicitis during a recent 28-month period by one of three pediatric surgeons or one of twenty general surgeons. Main Outcome Measures: Age, perforation rate, normal appendix rate, readmission rate, wound infection rate, postoperative abscess rate, hospital stay, hospital charges. Results: 304 children (65%) were treated by pediatric surgeons (Group 1) and 161 (35%) by general surgeons (Group 2). Group 1 patients were younger (8.3 ± 3.6 vs 13.2 ± 3.1 years, p < .001) and more likely to have gangrenous or perforated appendicitis (54% vs 33%, p < .001). There was no significant difference in the normal appendix rate (4.3% vs 5.6%, p = .53). In patients with simple, as well as complicated, appendicitis, there were no significant differences between Groups 1 and 2 in readmissions, postoperative complications, or hospital stay. Hospital charges were not significantly different for complicated appendicitis ($20, 527 vs $20, 254, p = .85) but were significantly lower for Group 1 patients with simple appendicitis ($10, 794 vs $12, 299, p = .002). Conclusions: In a children's hospital where both pediatric and general surgeons treat appendicitis, pediatric surgeons attend to younger patients with more severe appendicitis. There are no differences in outcomes for simple or complicated appendicitis between pediatric and general surgeons. Hospital charges are lower for simple appendicitis treated by pediatric surgeons.